Recommendations on percutaneous coronary intervention for the reperfusion of acute ST elevation myocardial infarction. Issue 6 (14th May 2004) - Montalescot, G; Andersen, H R; Antoniucci, D; Betriu, A; de Boer, M J; Grip, L; Neumann, F J; Rothman, M T
Abstract : Little information is currently available from the various societies of cardiology on primary percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI). Since primary PCI is the main method of reperfusion in AMI in many centres, and since of all cardiac emergencies AMI represents the most urgent situation for PCI, recommendations based on scientific evidence and expert experience would be useful for centres practising primary PCI, or those looking to establish a primary PCI programme. To this aim, a task force for primary PCI in AMI was formed to develop a set of recommendations to complement and assist clinical judgment. This paper represents the product of their recommendations.